Peran Orang Tua Asuh dalam Mebentuk Tingkah Laku Anak di Panti Asuhan Aisyiyah Batu Taba - Rahmi Rahmi; Afrinaldi Afrinaldi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
True values ​​and moral education is an education that a person gets from their immediate environment or can be called a child's first madrasah, namely from the family environment, especially parents. Children are an investment in the future whose growth and development must be optimally pursued. This article aims to describe the role of foster parents in educating values ​​and morals regarding children's behavior in the orphanage. Education is not obtained by individuals only at school, but from many places, namely the family and also the environment. The role of the family is very large, considering that the family is the child's closest environment, for this reason there needs to be special attention for the family, especially parents, in educating the child's character, as a basis for the child's behavior. Some things that parents need to pay attention to instill in their children from an early age are, the existence of clarity in instilling the values ​​taught to children, the existence of role models or providing good examples from parents, the existence of consequences for rules that have been applied consistently.